Hedgehog promotes cell proliferation in the midgut of silkworm, Bombyx mori. (7th May 2019) - Zhu, Shun‐Qin; Zhang, Ya‐Jun; Abbas, Muhammad Nadeem; Hao, Xiang‐Wei; Zhao, Yu‐Zu; Liang, Hang‐Hua; Cui, Hong‐Juan; Yang, Li‐Qun
Abstract: The Hedgehog (Hh) signaling pathway is one of the major regulators of embryonic development and tissue homeostasis in multicellular organisms. However, the role of this pathway in the silkworm, especially in the silkworm midgut, remains poorly understood. Here, we report that Bombyx mori Hedgehog ( BmHh ) is expressed in most tissues of silkworm larvae and that its functions are well‐conserved throughout evolution. We further demonstrate that the messenger RNA of four Hh signaling components, BmHh ligand, BmPtch receptor, signal transducer BmSmo and transcription factor BmCi, are all upregulated following Escherichia coli or Bacillus thuringiensis infection, indicating the activation of the Hh pathway. Simultaneously, midgut cell proliferation is strongly promoted. Conversely, the repression of Hh signal transduction with double‐stranded RNA or cyclopamine inhibits the expression of BmHh and BmCi and reduces cell proliferation. Overall, these findings provide new insights into the Hh signaling pathway in the silkworm, B. mori .